Forage intake by pregnant and lactating first-calf heifers - Linden, D.R.; Anderson, David E.; Pacheco, L.A.; Bolte, J.W.; Sproul, N.A.; Thomas, M.D.; Olson, K. C.; Jaeger, John R.; Holcomb, Kelsey L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forage dry matter intake by mature cows usually decreases during the final 4 to 8 weeks of gestation and then increases dramatically during the first 4 to 8 weeks of lactation. Rapid fetal growth during late pregnancy causes a physical impingement of the rumen. This reduction in ruminal capacity can cause prepartum reduction in forage intake. The rumen recovers its normal volume after calving. The increase in forage intake typical of the postpartum period is driven by milk production. Little research has focused on forage intake patterns by first-calf beef heifers during late gestation and early lactation. It is unknown if forage intake by growing heifers is similar to that of mature cows; moreover, poorly understood intake potential of heifers during the time preceding the second breeding season might contribute to the characteristically high rate of reproductive failure by these animals. Our objective was to measure the effects of advancing gestation and lactation on dry matter intake by first-calf heifers.
Keywords: Beef; Cattle; Dry matter intake; Gestation; Lactation; First-calf heifers